QUEUING CULTURE AND THE FORMING OF SOCIAL ATTITUDES IN MULTICULTURAL COMMUNITIES - Sukino Sukino (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
The culture of queuing is one of the activities in the public space and is symbolic, which can become the community's social capital towards a multicultural community cohesiveness. The people of Dak Jaya village have practiced the queuing culture for several moments. This study aims to explain the creation of the Dak Jaya Binjai Hulu village community when they are in line. The second explains the formation of people's social attitudes through queuing activities. This study is a field study that involves informal data collection tools, data obtained from interviews, and participant and non-participant observations. The results showed that the social reality of queuing, which became the best opportunity and became a non- material resource, were (1) queuing at the time of distributing BLT funds at the village office, (1) queuing at the gas station, (3) queuing at the Posyandu, (4) queuing at the market traditional and (5) queuing at the tahfid Quran stall. The queuing culture carried out by the Dak Jaya village community has provided space for the village community to develop social attitudes. The social attitudes that are built from the queuing culture are (1) queuing to train people to control themselves and be patient in taking rights, (2) queuing to grow public awareness of respecting time, (3) queuing to open communication spaces openly (silaturahim), (4) queuing to give creativity for cooperation and social care. The culture of queuing has a universal symbolic meaning, encouraging egalitarian principles of life in various conditions. Communities with a consistent queuing culture have the opportunity to achieve collective prosperity